COMPARISON OF LACTIC ACID BACTERIAL ISOLATES FROM VARIATIONS IN TIME FERMENTATION PROCESS OF CEMPEDAK SKIN - Syifa Noorwina; siti nashihah (Jurnal Insan Farmasi Indonesia, 2024)
Cempedak is a tropical native fruit from Indonesia and can be consumed by fermenting the skin fruit using a salt solution. The results of the fermentation called Mandai. Fermentation will be successful if there is a role of Lactic Acid Bacteria (LAB). Therefore, this study was conducted to determine the content of LAB in Mandai and isolates when fermented at different times. This study was carried out by dilution and the Pour Plate method, identifications such as morphological identification by gram staining and biochemical test by catalase t and TSIA test. Identification of this study was the observation of clear zone around the bacteria grown on MRSA media as a selective medium for LAB plus CaCO3. In this study, 5 samples of Mandai were used with different fermentation times. The results of the LAB isolation study in Mandai showed that the longer the Mandai fermentation was carried out, the more colonies there would be. While the LAB type was only found in sample 5 which was fermented within 20 weeks. The results obtained were following the characteristics of LAB, including gram-positive bacteria in the form of bacilli or cocci, not having catalase enzyme, and being able to ferment carbohydrates.